Trail network in Chiapas: linking people, ecosystems and ideas - Boné, Eduardo, speaker (Colorado State University. Libraries, 2014)
Chiapas is one of Mexico's most biologically and culturally diverse states, but also the poorest in the country. A vast network of pre-Colombian, colonial era and modern trails connect indigenous and rural communities throughout the state. It also functions as a natural corridor system used by wildlife connecting different protected areas ranging from rain and oak-pine forests to mangrove ecosystems. Unlike the USA, protected areas are inhabited and communally owned, and the role of the government is to promote wise land use and stewardship in partnership with local communities and private landowners. This seminar will present the results of "Caminando Chiapas", a project to use this network as a catalyst to diversify economic activities, build local capacities linked with ecotourism enterprises, as well as a tool to connect natural protected areas along the Mesoamerican Biological Corridor from Mexico to Panama. To date "Caminando Chiapas" has mapped 35 trails (171 miles) in Southeast Mexico and 22 trails (53 miles) in Panama creating alliances with local communities and authorities. We still have 6000 more miles to hike together!
Presented at the Spring 2014 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Innovations in Communities around the World", January 28, 2014, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Eduardo is a Mexican biologist interested in planning and management of natural areas, communication of science, environmental education and geographic information systems. He has worked in NGOs, governments, academia and the United Nations in Europe, Africa, Latin America and the United States since 2002. He is currently the Coordinator of the Conservation Leadership Through Learning (CLTL) master's program at CSU. As part of the 5th cohort of CCC fellows he is spearheading the creation of a transnational trail network to connect Mexico with Central America.
Recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.